IMPLEMENTASI MODEL PEMBELAJARAN NEEDHAM UNTUK MEMFASILITASI KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PADA MATERI OPERASI HITUNG PECAHAN - Fika Ramadhani; Nindy Citro Resmi; Mertika (EMTEKA: Jurnal Pendidikan Matematika, 2024)
This research aims 1) To find out whether there is an increase in the ability to understand concepts after implementing the NeedHam learning model for fifth grade students at SDN 93 with fraction counting operation material; 2) To find out how students' activities are during learning using the NeedHam learning model for class V students at SDN 93 Singkawang with fraction counting operation material; 3) To find out how the NeedHam learning model is implemented for class V students at SDN 93 Singkawang regarding fraction counting operations. The type of research is quantitative research with experimental methods and the design in this research is One Group Pretest Posttest Design. The population in this study were fifth grade students at SDN 93 Sigkawang. Samples were taken using saturated sampling. The data collection technique uses a test technique in the form of the ability to understand concepts and an observation technique using activity sheets and the implementation of the Needham model in the operation of calculating multiplication of fractions. The data analysis technique uses the N-Gain test, percentage of student learning activities and percentage of implementation. The results of the research show 1) There is an increase in students' understanding of mathematical concepts after implementing the Needham learning model to facilitate the ability to understand mathematical concepts in fraction multiplication calculation operation material in class V students at SDN 93 Singkawang; 2) Student learning activity is relatively high after implementing the Needham learning model in class V at SDN 93 Singkawang. This is proven by the results of the calculation of the average percentage obtained by the average value of the percentage of student learning activities for the first and second meetings, namely the calculation results obtained were 71.83%, which is in the high category; 3) the implementation of the Needham learning model was carried out well in the material on the operation of calculating multiplication of fractions in class V at SDN 93 Singkawang.